The immunomicrotope of Leishmania control and persistence - Bogdan, Christian; islam, Noor-A-kasida; Barinberg, David; Soulat, Didier; Schleicher, Ulrike; Rai, Baplu (Trends in Parasitology, 2024)
Leishmania is an intracellular protozoan transmitted by sand fly vectors; it causes cutaneous, mucocutaneous, or visceral disease. Its growth and survival are impeded by type 1 T helper cell responses, which entail interferon (IFN)-γ-mediated macrophage activation. Leishmania partially escapes this host defense by triggering immune cell and cytokine responses that favor parasite replication rather than killing. Novel methods for in situ analyses have revealed that the pathways of immune control and microbial evasion are strongly influenced by the tissue context, the micro milieu factors, and the metabolism at the site of infection, which we collectively term the ‘immunomicrotope’. Understanding the components and the impact of the immunomicrotope will enable the development of novel strategies for the treatment of chronic leishmaniasis.
CRIS-Team Scopus Importer:2024-09-13
Keywords: evasion; immunity; Leishmania parasites; leishmaniasis; micro milieu factors; persistence